PROCESSING OF THE PROCESSING INFORMATION SYSTEM POPULATION DATA IN KATURAHAN KATIAHAN WEBMOBILE BASED - Ahmad Sobri; Hasanah Tri (STMIK Pringsewu Lampung, 2019)
Management of population administration data of related institutions plays an important role in the process of collecting population data that is relevant and can be a guide for an area that is related to the population census. In this case the population data system is one of the factors that influences population data in the area of Air Kati Village, Lubuklinggau Selatan I District, Lubuklinggau City. Air Kati Urban Village in conducting population data collection still uses manual methods, namely by visiting residents one by one to find out the number of each family head. If the data collection officer comes to a resident's house often experiences obstacles, there is no person or family head in the house. This has become an obstacle for officials in assessing population data to collect data quickly. Based on this observation the author's desire arises to create an information system that can help officers in population data collection in Air Kati village, Lubuklinggau Selatan I District, Lubuklinggau City. The purpose of this study is expected to process the management of population information systems in the data collection that is done quickly and effectively. With the web mobile based population information system design, it can facilitate the admin in inputting administrative data of the family head community in Air Kati Urban Village, reducing the time needed, reducing the possibility of errors in recording and speeding up the search process